Identification of MicroRNA–mRNA Networks in Melanoma and Their Association with PD-1 Checkpoint Blockade Outcomes - Robert A. Szczepaniak Sloane (MDPI AG, 2021)
Metastatic melanoma is a deadly malignancy with poor outcomes historically. Immuno-oncology (IO) agents, targeting immune checkpoint molecules such as cytotoxic T-lymphocyte associated protein-4 (CTLA-4) and programmed cell death-1 (PD-1), have revolutionized melanoma treatment and outcomes, achieving significant response rates and remarkable long-term survival. Despite these vast improvements, roughly half of melanoma patients do not achieve long-term clinical benefit from IO therapies and there is an urgent need to understand and mitigate mechanisms of resistance. MicroRNAs are key post-transcriptional regulators of gene expression that regulate many aspects of cancer biology, including immune evasion. We used network analysis to define two core microRNA–mRNA networks in melanoma tissues and cell lines corresponding to ‘MITF-low’ and ‘Keratin’ transcriptomic subsets of melanoma. We then evaluated expression of these core microRNAs in pre-PD-1-inhibitor-treated melanoma patients and observed that higher expression of miR-100-5p and miR-125b-5p were associated with significantly improved overall survival. These findings suggest that miR-100-5p and 125b-5p are potential markers of response to PD-1 inhibitors, and further evaluation of these microRNA–mRNA interactions may yield further insight into melanoma resistance to PD-1 inhibitors.